Energy taxation policies can counteract the rebound effect: analysis within a general equilibrium framework - Jaume Freire-González (Energy Efficiency, 2019)
The rebound effect reflects the difference between the expected energy savings from energy efficiency, and the real ones, considering the former is higher than the latter. In some extreme cases, some scholars consider energy use can even increase after an energy efficiency improvement. This is due to agents' behavioural responses. After almost four decades of theoretical and empirical studies in the field, there is a strong consensus amongst energy economists that the rebound effect of energy efficiency exists, although its importance is still being discussed. However, there are few empirical studies exploring its potential solutions. In this research we empirically assess the effects of energy taxation on the rebound effect. Using a dynamic energy-economy computable general equilibrium (CGE) model of the Spanish economy, we test a global energy efficiency increase of 5.00%, and at the same time, different ad valorem tax rates on energy industries. We find that a tax rate of 3.76% would totally counteract the economy-wide rebound effect of 82.82% we estimate for the Spanish economy. This tax rate would still allow some economic benefits provided by the increase of energy productivity.
Keywords: 330